Social Support in Patient Adherence on Hypertension Management - Sapto Haryatmo; Ratna Sitorus; Yulia Yulia (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Patient compliance with hypertension management is important because non-adherence can lead failure to control blood pressure. This study aims to identify demographic factors and social support in relation to hypertension management adherence. This research is a non-experimental cross sectional analytic study to a population of hypertensive patients in the Temanggung region. Sampling used concecutive sampling with 100 respondents. The Adherence variable was measured using a Medical Outcomes Study (MOS) Measures of Patient Adherence and social support was measured using the Multidimensional Scale of Perceived Social Support. Data were analyzed univariately, bivariately and multivariately to determine the significance and strength of variable correlation. Research result shows a significant relationship between education level (p value = 0.014) and social support (p value = 0.013) with adherence. There was no significant correlation between age (p value = 0.982), gender (p value = 0.435) and financing (p value = 0.521) with adherence. Multivariate test results showed that social support was significantly related to adherence with p value = 0.028 at α = 0.05. Social support has an odds ratio of 5.8, which means patients with good social support have a 5.8 times chance to be more obedient.